Analysis of Squeezing Phenomenon in the Headrace Tunnel of Chameliya Project, Nepal - Shrestha, Pawan Kumar; Panthi, Krishna Kanta; Basnet, Chhatra Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
The headrace tunnel of Chameliya Hydroelectric Project, Nepal has faced severe squeezing problems from chainage 3+100m to 3+900m. Due to the severe squeezing and deformation, the tunnel cross section has narrowed considerably along this 800m long tunnel stretch. The tunnel wall closure (deformation) is mostly well over 1 m and the maximum recorded closure exceeds 2m. This paper assesses the squeezing phenomenon along this tunnel stretch through evaluation of rock mass properties and support pressure. Three different methods (two analytical and one 2D finite element numerical modeling program) are used in this analysis. The finding is that it is possible to predict extent of squeezing in tunnel if more than one method is used to verify rock mass mechanical properties. DOI: http://dx.doi.org/10.3126/hn.v13i0.10039 HYDRO NEPAL Journal of Water, Energy and Environment Issue No. 13, July 2013 Page: 44-51 Uploaded date: 3/13/2014